Synthesis and biological evaluation of novel PET tracers [18F]AG120 & [18F]AG135 for imaging mutant isocitrate dehydrogenase 1 expression. (1st January 2022) - Wang, Tingting; Lin, Qingyu; Zhang, Yingying; Xu, Zhan; Shi, Dai; Cheng, Yuan; Fu, Zhequan; Tan, Hui; Cheng, Dengfeng; Shi, Hongcheng
Graphical abstract: 18 F-labeled IDH1 mutation inhibitor [ 18 F]AG120 was successfully developed and evaluated, and exhibited specific targeting to IDH1 mutant tumor model with positron emission tomography imaging. Abstract: Mutations in isocitrate dehydrogenase 1 (IDH1) are commonly found in various human malignancies. Inhibitors of several mutant IDH1 enzymes have entered clinical trials as target therapeutic drugs for the treatment of patients with IDH1 mutations. Herein, we report the synthesis and evaluation of two 18 F-labeled tracers, [ 18 F]AG120 and [ 18 F]AG135 for imaging expression of mutated IDH1 in positron emission tomography (PET). [ 18 F]AG120 and [ 18 F]AG135 were synthesized in decay-corrected radiochemical yield of 1 % and 3 %, respectively, high molar activity (52–66 MBq/nmol and 216–339 MBq/nmol, respectively) and high radiochemical purity (>99%). Both tracers showed good in vitro stability, selective uptake into mutated IDH1-expressing cells and good pharmacokinetic profiles with low uptake in most organs/tissues. Furthermore, [ 18 F]AG120 micro-PET/CT imaging displayed significantly greater uptake in IDH1-mutant than in wild-type tumors, Relatively, uptake of [ 18 F]AG135 was observed neither in IDH1-mutant tumor xenografts nor in wild-type tumors. This study suggests that [ 18 F]AG120 is a promising radiotracer for PET imaging of IDH1 mutation, However, further optimization and investigation are necessary for [ 18 F]AG135 due to the limited uptake in mutated IDH1-expressing tumors.